Analysis of factors affecting completion of growth processes in the post-puberty period - E. V. Kruglikova; E. A. Chanchaeva; R. I. Aizman (Сибирский научный медицинский журнал)
Post-puberty age is characterized by the formation of a definitive level of morphofunctional indicators of the body, the processes of social adaptation to a new after school stage of life and level of education. For age-related physiology, the post-puberty age is of interest in terms of the timing of completion of growth processes, as well as factors that determine these boundaries. Differences in the timing of completion of growth processes in juvenile age are due not only to a genetic factor, but also to a complex of epigenetic effects. This paper analyzes the literature data on factors that determine the timing of stabilization of growth processes in post-puberty age. The results of the analysis allow us to scientifically justify the conditions for the full implementation of the genotypic trait of long body size. Modern ideas about humoral mechanisms of growth regulation indicate the relationship between the secretion of growth factors and environmental conditions. Numerous studies prove the association of growth hormone with the stage of delta sleep and physical activity, somatomedin-C-with a protein diet. Growth hormone synergists in certain concentrations are insulin, sex and thyroid hormones, while glucocorticoids are antagonists. These factors allow us to explain the secular variability of the longitudinal body parameters of the generations in 19th-20th and 20th-21st centuries, depending on socio-economic conditions, lifestyle, puberty, and nutrition. The significance of the genetic factor is confirmed by differences in the timing of stabilization of body length between populations of different racial and ethnic backgrounds, and the sensitivity of growth processes to environmental factors is appeared between different geographical latitudes populations. Therefore, along with the genetic factor, climatic and geographical conditions, food quality, sleep and wake patterns, and lifestyle are determinants that affect the variability in the timing of growth processes completion in postpubertal age.